"Don't look down on us!": Assessing the vulnerabilities of female massage parlor workers in Phnom Penh, Cambodia. Issue 1 (2nd December 2019) - Miles, Glenn Michael; Blase, Olivia; Clark, Katie; Ding, Rachel J.; Geyer, Theresa
Abstract : Purpose: Although some research has been done with entertainment workers in KTV bars, little has been done to gain a qualitative understanding of the vulnerabilities of masseuse women. This is due to a prevalent focus on girls under 18 years, thereby excluding most masseuses. The paper aims to discuss these issues. Design/methodology/approach: In total, 98 female participants completed an interview answering both open and closed questions concerning relationships, stigma and discrimination and personal sexual abuse among other topics. Findings: This study finds that many women working in the massage parlor industry are vulnerable to various threats, including sexual exploitation and abuse. Dependency structures within the massage parlor as well as with their families seem to play a key role in the life situations that can be positive as well as negative, and in some cases both. Social implications: The findings provide a baseline evaluation of the vulnerable conditions of the massage industry for women in Cambodia. Specifically, that stigma, discrimination, physical and sexual abuse, as well as a lack of access to education are all vulnerabilities not commonly covered, especially with adult women working in the entertainment industry. This research has been adapted from the original transcript "Strive, No Matter What" (Miles et al., 2014). Originality/value: The paper seeks to understand the reality of life and vulnerabilities as perceived by Phnom Penh's female masseuses in the lower-priced massage parlors which is largely unknown.